KAJIAN TERHADAP RUANG PEMBELAJARAN DI SMK JURUSAN BANGUNAN DI DAERAH ISTIMEWA YOGYAKARTA - Sativa Sativa (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2010)
At the time, the need of skilled humans as industrial resources is very high.Therefore, the government makes many policies to increase the quality of vocational schools which produce those skilled human resources, especially in building industry. Because of that, it is also important to improve the quality of the educational infrastructure, especially at building vocational schools. This research aimed to study theory and practical room conditions at a number of building vocational schools in Yogyakarta Special Province. Focuses of the study were room dimension, furniture lay out, audio comfort, thermal comfort, natural and artificial lighting, and also natural vent. This research used rasionalistic approachment, evaluation method and involved a number of students. To gain data, there were used documentation, observation, and measurement. The study on four building vocational haigh schools as cases study resulted that not all of learning rooms achieved a comfort standard, especially in thermal condition, vents, lighting and noising.Keywords: evaluation, learning rooms, building vocational high schools,